ALGORITHMIC ENUMERATION OF PROBLEMS IN THE CLASS NPcoNP - V. G. Naidenko (Informatika)
The problem of recursive (algorithmic) representation is considered for the complexity class NPcoNP. A new method is proposed for algorithmically enumerating all problems in NPcoNP, using polynomial-time nondeterministic Turing machines.